2019
DOI: 10.1038/s41598-019-51416-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Coffee Farms to Hurricane Maria: Resistance and Resilience from an Extreme Climatic Event

Abstract: Resistance and resilience have become important concepts in the evaluation of disturbance events, providing a framework that is useful in light of the expected increase in frequency and occurrences of hurricanes as a consequence of climate change. Hurricane Maria landed on Puerto Rico as a category 4 storm in September of 2017. Among the affected elements were agricultural systems, including coffee agroecosystems. Historically, coffee has been a major backbone of the island’s agricultural sector. Grown with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…The study found that coffee farmers' recovery after Maria was potentiated by assistance from their social and community networks of support. And that management style may come secondary in a catastrophic context (Perfecto et al, 2019). Nevertheless, our qualitative analysis suggests that farmers may have been constrained in accessing such networks, which likely affected their overall capacity for recovery.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The study found that coffee farmers' recovery after Maria was potentiated by assistance from their social and community networks of support. And that management style may come secondary in a catastrophic context (Perfecto et al, 2019). Nevertheless, our qualitative analysis suggests that farmers may have been constrained in accessing such networks, which likely affected their overall capacity for recovery.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, our analysis suggests that farmers also faced challenges when accessing social networks of support, likely further challenged by the lack of material resources and technology. Perfecto et al (2019) assessed how coffee farms' management, whether incorporating agroforestry or performing an intensive style, related to the degree of damages experienced and farm recovery after Maria. The study found that coffee farmers' recovery after Maria was potentiated by assistance from their social and community networks of support.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers in Latin America [ 67 , 68 ], and the Caribbean [ 70 , 71 ] have been noted to lack institutional structures of support. In Puerto Rico, Perfecto and colleagues (2019) found that social capital and support networks were pivotal for Puerto Rican coffee farmers’ recovery after Hurricane María, and that their agroecological practices, such as agroforestry, and other management styles were not sufficient for farms to be resilient and resistant within the catastrophic context of Hurricane Maria [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such agricultural gains were important since Puerto Rico, like the broader Caribbean, was experiencing a steady decline in farms since the 1990's due to trade liberalization, globalization, and other external and local forces [18,49,50,51,52]. Nevertheless, such gains were erased when both Hurricane Irma and Hurricane Maria, two of the strongest in the Atlantic's history, hit Puerto Rico in September 2017 [46,[53][54][55].…”
Section: The Present Studymentioning
confidence: 99%
“…have been noted to lack institutional structures of support. In Puerto Rico,Perfecto and colleagues (2019) found that social capital and support networks were pivotal for Puerto Rican coffee farmers' recovery after Hurricane María, and that their agroecological practices, such as agroforestry, and other management styles were not sufficient for farms to be resilient and resistant within the catastrophic context of Hurricane Maria[70]. Hurricane María affected all of Puerto Rico, causing 2,975 deaths[71], and decimated the archipelago's agriculture.…”
mentioning
confidence: 99%